Crafting a Job: Revisioning Employees as Active Crafters of Their Work - Wrzesniewski, Amy; Dutton, Jane E. (Academy of Management Review, 2001)
We propose that employees craft their jobs by changing cognitive, task, and/or relational boundaries to shape interactions and relationships with others at work. These altered task and relational configurations change the design and social environment of the job, which, in turn, alters work meanings and work identity. We offer a model of job crafting that specifies (1) the individual motivations that spark this activity, (2) how opportunities to job craft and how individual work orientations determine the forms job crafting takes, and (3) its likely individual and organizational effects.